Composite silver plating brush plating solution and composite silver plating brush plating method

By using a composite silver plating brush plating solution to form a silver-molybdenum disulfide composite plating layer on the copper base surface of the isolation switch of the power transmission and transformation equipment, the problem that the existing silver plating layer cannot have high conductivity, high wear resistance and high corrosion resistance at the same time, achieving higher corrosion resistance and wear resistance, reducing overtemperature risks and operating costs.

CN119615308APending Publication Date: 2025-03-14ELECTRIC POWER RESEARCH INSTITUTE OF STATE GRID JIBEI ELECTRIC POWER CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411706263.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-14

Smart Images

  • Figure BDA0005154581740000111
    Figure BDA0005154581740000111
  • Figure BDA0005154581740000121
    Figure BDA0005154581740000121
  • Figure BDA0005154581740000131
    Figure BDA0005154581740000131
Patent Text Reader

Abstract

The invention provides a composite silver plating brush plating solution and a composite silver plating brush plating method. The brush plating solution comprises the following raw materials: silver nitrate, molybdenum disulfide, formaldehyde and a solvent, on the basis of the volume of the brush plating solution, the content of silver nitrate is 40-60 g.L <-1 >, the content of molybdenum disulfide is 5-30 g.L <-1 >, and the content of formaldehyde is 10-20 g.L <-1 >. The composite silver plating brush plating method comprises the following steps: performing brush plating on the surface of a workpiece by using the composite silver plating brush plating solution, and forming a silver-molybdenum disulfide composite plating layer on the surface of the workpiece. According to the technical scheme provided by the invention, by plating the silver-molybdenum disulfide composite coating on the copper-based surface of the isolation switch of the power transmission and transformation equipment, the conductivity of the copper-based component is improved, the contact resistance of the copper-based component is reduced, the overtemperature and overheat generation frequency and period of the copper-based component are reduced, the heating treatment cost of a transformer substation is reduced, and the service life of the transformer substation is prolonged. And long-period, safe and stable operation of the power grid is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electric contact material preparation, and in particular relates to a composite silver-plating brush plating solution and a composite silver-plating brush plating method for a disconnector of power transmission and transformation equipment. Background Art

[0002] The concentration of sulfur dioxide in the atmosphere is high in some areas. In some places, the concentration of sulfur dioxide is as high as 20mg / L-30mg / L, and in some areas it even exceeds 40mg / L. The atmospheric environment with high sulfur dioxide concentration will cause serious sulfidation and corrosion to the electrical contact parts in the power transmission and transformation equipment, causing the contact resistance to increase, which will cause the contact parts to fail due to a sudden increase in heat or direct non-conductivity. There are a large number of electrical contact parts of electrical equipment in the power grid, such as high-voltage disconnectors, terminal blocks, busbar connectors, wire clamps, etc., some of which are treated with silver plating and tin plating on the surface. Operation and maintenance have found that electrical contacts often suffer from overheating and excessive contact resistance due to surface corrosion and wear. Replacing new electrical contacts is not only a waste of resources, but also requires on-site secondary processing and the process is cumbersome. Therefore, electrical contacts are often repaired by grinding to remove corrosion products and applying conductive paste, but the conductive paste is easy to flow and solidify and loses its resistance reduction effect, resulting in hot spots that are difficult to cure and reappear repeatedly.

[0003] At present, silver plating is generally used in electrical contact parts such as high-voltage disconnectors. The wear resistance, corrosion resistance and insufficient adhesion of the silver plating are one of the main reasons for the peeling of the silver plating, copper exposure and heating. For high-voltage disconnectors, the silver plating quality of its contact system is a key indicator, which is directly related to the service life and service reliability of the high-voltage disconnector. The existing silver plating technology of disconnectors for power transmission and transformation equipment includes: (1) plating a pure silver layer on the surface of the copper-based moving and static contacts of the disconnector; pure silver has good conductivity, and plating a pure silver layer can enhance the conductivity of the disconnector, reduce contact resistance, and ensure the flow efficiency of the knife switch; however, due to its inherent limitations (low hardness and insufficient adhesion), the pure silver plating has average wear resistance and bonding, and is very easy to form corrosion products with poor conductivity in a corrosive environment, which is very easy to cause the pure silver to separate during the switching process of the moving and static contacts, resulting in copper exposure and heating. (2) The surface of the copper-based moving and static contacts of the disconnector is plated with a silver-metal oxide layer; the silver-metal oxide coating has higher hardness and wear resistance than the pure silver coating. Commonly used silver-metal oxide coatings include Ag-MeO (silver-metal oxide) coating, Ag-RE (silver-rare earth) coating, and Ag-WC (silver-tungsten disulfide) coating; adding metal oxides to the silver coating can improve the high temperature resistance of the electroplating layer, resist arc erosion of the disconnector, and extend the life of the disconnector. However, the density and conductivity of the silver-metal oxide coating are poor. (3) The surface of the copper-based moving and static contacts of the disconnector is plated with a silver-non-metal layer, such as silver-graphite coating, silver-graphene coating, silver-carbon nanotube layer, etc.; the conductivity of the silver-non-metal layer is improved, but due to the poor dispersion of the non-metal in the coating, the silver-non-metal coating is not dense enough, which affects its wear resistance and corrosion resistance.

[0004] In summary, the silver plating layer of the existing power transmission and transformation equipment disconnector generally has the problem of not being able to simultaneously possess high conductivity, high wear resistance, and high corrosion resistance. Summary of the invention

[0005] The object of the present invention is to provide a composite silver plating technical solution suitable for isolating switches of power transmission and transformation equipment, which can ensure conductivity while having high wear resistance and high corrosion resistance.

[0006] In order to achieve the above object, the present invention provides the following technical solutions.

[0007] In a first aspect, the present invention provides a composite silver-plating brush plating solution, wherein the raw material composition of the brush plating solution includes: silver nitrate, molybdenum disulfide, formaldehyde, and a solvent;

[0008] Based on the volume of the brush plating solution, the content of silver nitrate is 40-60g·L -1 , the content of molybdenum disulfide is 5-30g·L -1 , the formaldehyde content is 10-20g·L -1 .

[0009] The composite silver-plating brush plating liquid provided by the present invention can realize the preparation of silver-molybdenum disulfide composite coatings. Molybdenum disulfide is an important solid lubricant with good chemical stability and thermal stability, and is suitable for high temperature and high pressure environments; it also has self-lubricating properties, which can significantly improve the tribological properties of silver-based composite materials and play a role in reducing friction and resisting wear; in addition, molybdenum disulfide can also be used as a semiconductor material, and has the functions of rectification and energy conversion. In short, molybdenum disulfide has excellent electrical conductivity, wear resistance, and corrosion resistance. Molybdenum disulfide particles fill the larger pores between silver particles in the coating, effectively preventing external corrosive media from entering the pure silver coating, thereby improving its corrosion resistance and anti-sulfur ability. A silver-molybdenum disulfide composite structure is formed in the silver-molybdenum disulfide composite coating. This composite structure is used for surface plasma applications and shows excellent performance. This composite structure not only improves the electrical conductivity of the material, but also enhances its tribological properties and wear resistance. The silver-molybdenum disulfide composite coating prepared by the composite silver-plating brush plating solution provided by the present invention introduces molybdenum disulfide particles into the silver-based coating, thereby significantly improving the corrosion resistance and wear resistance of the coating while ensuring the conductive performance of the coating. After the composite silver-plating brush plating solution provided by the present invention forms a silver-molybdenum disulfide composite coating on the surface of a copper-based electrical contact component, the contact resistance of the copper-based electrical contact component is reduced, the wear resistance and corrosion resistance of the coating are improved, the frequency and period of overheating of the copper-based electrical contact component are reduced, the cost of heat treatment of the substation is reduced, and the long-term, safe and stable operation of the power grid is ensured.

[0010] According to a specific embodiment of the first aspect, preferably, based on the volume of the brush plating solution, the content of molybdenum disulfide is 20-25 g·L -1 This preferred technical solution can achieve a higher bonding rate between molybdenum disulfide and the silver-plated layer, a lower porosity of the coating, better prevention of external corrosive media from entering the coating, improved electrodeposition efficiency, and improved corrosion resistance of the composite coating.

[0011] According to a specific implementation of the first aspect, preferably, the mass ratio of silver nitrate, molybdenum disulfide and formaldehyde is 10:5:3.

[0012] According to a specific implementation of the first aspect, preferably, the molybdenum disulfide is selected from hexadecyltrimethylammonium bromide modified nano molybdenum disulfide;

[0013] More preferably, the hexadecyltrimethylammonium bromide modified nano molybdenum disulfide is prepared by the following method:

[0014] Mixing nano-molybdenum disulfide particles, hexadecyltrimethylammonium bromide, and an alcohol solvent; heating the obtained mixture to reflux and standing to react in sequence; performing solid-liquid separation on the product obtained after the reaction; washing and drying the solid phase obtained by the solid-liquid separation to obtain the hexadecyltrimethylammonium bromide-modified nano-molybdenum disulfide;

[0015] Further preferably, the temperature of the heating reflux reaction is 75-85°C;

[0016] Further preferably, the heating reflux reaction time is 22-26h;

[0017] Further preferably, the temperature of the static reaction is room temperature;

[0018] Further preferably, the static reaction time is 22-26h;

[0019] Further preferably, the alcohol solvent is ethanol;

[0020] Further preferably, the mass ratio of nano-molybdenum disulfide particles to hexadecyltrimethylammonium bromide is 1-6:1;

[0021] MoS2 has a layered structure, and its large specific surface area and high specific surface energy make it easy to agglomerate to form larger particles, which has poor dispersibility, thus affecting its performance. Hexadecyltrimethylammonium bromide (CTAB), as a cationic surfactant, can be inserted into the interlayers of MoS2 and attached to the surface of MoS2 through electrostatic attraction. Hexadecyltrimethylammonium bromide is inserted into the interlayers of MoS2 through electrostatic attraction, which can increase the interlayer spacing, expose more sulfur atoms and active sites, and thus enhance the adsorption capacity and reaction activity. Hexadecyltrimethylammonium bromide is attached to the surface of MoS2 through electrostatic attraction, and bonds to the hydrophilic functional group carboxyl on the surface of MoS2, which can reduce the surface energy of MoS2, thereby improving the dispersibility and stability of MoS2 in the brush plating solution, preventing the agglomeration of MoS2, and making the MoS2 particles more evenly distributed in the coating and filling the larger pores of the silver coating. Hexadecyltrimethylammonium bromide acts as a template in the coating formation process, helping to form a regular nanostructure, optimizing the morphology of the coating and the dispersibility of the nanoparticles. Nano-molybdenum disulfide modified with hexadecyltrimethylammonium bromide can further improve the mechanical properties of the coating.

[0022] According to a specific implementation of the first aspect, preferably, the raw material composition of the brush plating solution further includes nickel salt; based on the volume of the brush plating solution, the content of the nickel salt is 100-120 g·L -1 ; Nickel salt provides nickel ions, which helps to improve the conductivity and stability of the plating solution;

[0023] More preferably, the nickel salt comprises NiSO4·6H2O and NiCl2·6H2O;

[0024] Further preferably, based on the volume of the brush plating solution, the content of NiSO4·6H2O is 80-100 g·L -1 ;

[0025] Further preferably, based on the volume of the brush plating solution, the content of NiCl2·6H2O is 10-30 g·L -1 .

[0026] According to a specific implementation of the first aspect, preferably, the raw material composition of the brush plating solution further includes boric acid; based on the volume of the brush plating solution, the content of boric acid is 5-15 g·L -1 ; Boric acid acts as a buffer to maintain the pH value of the plating solution stable.

[0027] According to a specific implementation of the first aspect, preferably, the raw material composition of the brush plating solution further includes sodium sulfate; based on the volume of the brush plating solution, the content of sodium sulfate is 30-50 g·L -1 ; Sodium sulfate can increase the conductivity of brush plating solution.

[0028] According to a preferred embodiment of the first aspect, preferably, the solvent is water.

[0029] In a second aspect, the present invention provides a method for preparing the composite silver-plating brush plating solution provided in the first aspect, the preparation method comprising:

[0030] The composite silver-plating brush plating solution is obtained by mixing silver nitrate, formaldehyde and part of the solvent and then adding other components in the brush plating solution.

[0031] In a third aspect, the present invention provides a composite silver-plating brush plating method, the method comprising:

[0032] The composite silver-plating brush plating solution provided by the first aspect of the present invention is used to perform brush plating on the surface of a workpiece to form a silver-molybdenum disulfide composite coating on the surface of the workpiece.

[0033] According to the specific implementation method of the third aspect, brush plating is carried out using a brush plating machine. First, the substrate to be brush plated is connected to the negative pole of the power supply as the cathode, and the brush plating pen (with a sheath) connected to the positive pole of the power supply is immersed in the brush plating solution as the anode. Relying on the action of direct current, the brush plating pen maintains contact with the workpiece under a certain pressure and performs relative movement during brush plating. The metal cations in the brush plating solution in the bath will be discharged and crystallized on the substrate to be brush plated as the cathode to form a coating. After the brush plating is completed, rinse with water, then rinse with alcohol, and finally blow dry. The high-frequency mechanical vibration of the ultrasonic cleaning machine is used to clean the oil wrapped on the surface of the sample, the adhering impurities and the attached fingerprints.

[0034] According to a specific embodiment of the third aspect, preferably, in the process of brush plating on the surface of a workpiece using the composite silver plating brush plating solution provided by the first aspect of the present invention, the working voltage of the brush plating is 3-5V, and the relative movement speed between the brush plating pen and the workpiece is 2-4m·min -1 , current density is 0.1-0.5A·dm -2The electroplating time is 2-4 minutes, and the specific time is determined according to the required coating thickness; this method can preferably control the brush plating conditions to prepare a more uniformly dispersed coating, thereby further improving the corrosion resistance of the coating.

[0035] According to a specific implementation of the third aspect, preferably, the thickness of the silver-molybdenum disulfide composite coating formed on the surface of the workpiece is 30-40 μm.

[0036] According to a specific embodiment of the third aspect, preferably, the composite silver-plating brush plating method further comprises:

[0037] Before using the composite silver-plating brush plating solution provided by the first aspect of the present invention to perform brush plating on the surface of the workpiece, surface treatment is performed on the surface of the workpiece;

[0038] More preferably, the surface treatment of the workpiece surface comprises: grinding, etching, electro-cleaning and activation of the workpiece surface in sequence;

[0039] Grinding treatment can effectively remove surface dirt and oxides to ensure a bright and rust-free surface; etching treatment can produce slight etching on the surface, which is conducive to improving the adhesion between the substrate surface and the coating; electro-cleaning treatment can dissolve grease and oil stains on the surface; activation treatment can remove the oxide film and fatigue layer on the substrate surface;

[0040] More preferably, the grinding process includes: coarse grinding, fine grinding and polishing in sequence; further preferably, the coarse grinding is performed using 800# sandpaper, the fine grinding is performed using 1000# sandpaper, and the polishing is performed using 1200# sandpaper;

[0041] More preferably, the etching treatment includes sequentially performing a hydrochloric acid soaking treatment and an alkaline solution soaking treatment; further preferably, the hydrochloric acid soaking treatment includes sequentially using hydrochloric acid with a HCl mass concentration of 50% to soak at 60°C for 5-10min and at 70°C for 5-10min; further preferably, the raw material composition of the alkaline solution used in the alkaline solution soaking treatment includes NaOH, Na2SO4, Na2CO3, Na2SiO3 and water; based on the volume of the alkaline solution, the content of NaOH is 2-5g·L -1 , the content of Na2SO4 is 35-55g·L -1 , the content of Na2CO3 is 30-50g·L -1 , the content of Na2SiO3 is 10-20g·L -1 ;

[0042] More preferably, the working voltage of the electro-cleaning treatment is 8-12V and the working time is 30-40s;

[0043] More preferably, the raw material composition of the electro-cleaning liquid used in the electro-cleaning treatment includes sodium hydroxide, sodium carbonate, sodium phosphate, sodium silicate and water; based on the volume of the electro-cleaning liquid, the content of sodium hydroxide is 10-45g·L -1 , the content of sodium carbonate is 11-18g·L -1 , the content of sodium phosphate is 25-35g·L -1 , the content of sodium silicate is 2-15g·L -1 ;

[0044] More preferably, the activation treatment has an operating voltage of -12V to -8V and a working time of 30-40s;

[0045] More preferably, the raw material composition of the activation solution used in the activation treatment includes hydrochloric acid, sodium chloride and water; based on the volume of the activation solution, the content of hydrochloric acid is 15-30g·L -1 , the content of sodium chloride is 110-145g·L -1 .

[0046] According to a specific implementation of the third aspect, preferably, the surface material of the workpiece is copper.

[0047] In a fourth aspect, the present invention provides a composite coating, wherein the composite coating is prepared using a composite silver-plating brush plating method provided in the third aspect of the present invention.

[0048] The technical solution provided by the technical solution of the present invention can effectively realize the coating of a silver-molybdenum disulfide composite coating on the copper-based surface of the power transmission and transformation equipment disconnector with high wear resistance and high corrosion resistance while ensuring conductivity. The molybdenum disulfide particles in the silver-molybdenum disulfide composite coating fill the larger pores between the silver nanoparticles, making the coating more dense, effectively preventing external corrosive media from entering the coating, thereby improving its corrosion resistance and anti-sulfur ability, effectively improving the wear resistance of the coating, and effectively improving the conductivity of the coating. The technical solution of the present invention improves the conductivity of copper-based components, reduces the contact resistance of copper-based components, reduces the frequency and period of overheating of copper-based components, reduces the cost of heat treatment in substations, and ensures long-term, safe and stable operation of the power grid by coating the silver-molybdenum disulfide composite coating on the copper-based surface of the power transmission and transformation equipment disconnector. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 Schematic diagram of the Tafel polarization curves of the pure silver coating of Comparative Example 1 and the composite coating of Example 1.

[0050] Figure 2 Schematic diagram of the Tafel polarization curves of the composite coatings of Example 1, Example 4, and Example 7.

[0051] Figure 3Schematic diagram of the Tafel polarization curves of the composite coatings of Example 1, Example 2, and Example 3.

[0052] Figure 4 Schematic diagram of the equivalent circuit of impedance spectroscopy test.

[0053] Figure 5 It is the Nyquist diagram of impedance diagram of the composite coating of Example 1 to Example 9.

[0054] Figure 6 It is a Bode modulus diagram of impedance schematic spectrum of the composite coating of Example 1 to Example 9.

[0055] Figure 7 It is the impedance schematic spectrum phase angle diagram of the composite coating of Example 1 to Example 9.

[0056] Figure 8 These are cross-sectional morphology diagrams of the composite coatings of Example 10, Example 12, Example 14, and Example 15.

[0057] Fig. 9 This is the SEM scanning image of the composite coating of Example 10-Example 15.

[0058] Fig.10 Schematic diagram of the Tafel polarization curves of the composite coatings of Examples 10 to 15.

[0059] Fig.11 Schematic diagram of the equivalent circuit of impedance spectroscopy test.

[0060] Fig.12 This is the Nyquist diagram of the impedance diagram of the composite coating of Example 10 to Example 15.

[0061] Fig.13 This is a Bode modulus diagram of the impedance schematic spectrum of the composite coating of Example 10 to Example 15.

[0062] Fig.14 It is the impedance schematic diagram spectrum phase angle diagram of the composite coating of Example 10-Example 15.

[0063] Fig.15 This is the XRD spectrum of the composite coating of Example 10-Example 15.

[0064] Fig.16 1 and 2 are XRD spectra of the composite coatings of Example 1, Example 2, Example 3 and Example 16.

[0065] Fig.17 This is the EDS energy spectrum and element distribution diagram of the composite coating of Example 2.

[0066] Fig.18These are the surface morphologies of the coatings of Example 1, Example 16, and Comparative Example 1 after testing on a reciprocating sliding friction and wear testing machine. DETAILED DESCRIPTION

[0067] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present invention.

[0068] Example 1

[0069] This embodiment provides a composite silver-plating brush plating method, wherein the method comprises:

[0070] 1. Surface treatment of the aluminum-based surface of the electrical contact parts, including:

[0071] The surface of the copper-based workpiece is subjected to grinding, etching, electro-cleaning and activation treatments in sequence;

[0072] Among them, the dimensions of the copper-based workpiece surface are 30 mm wide × 100 mm long × 1 mm thick;

[0073] The grinding process includes: coarse grinding, fine grinding and polishing in sequence; the coarse grinding is performed using 800# sandpaper, the fine grinding is performed using 1000# sandpaper, and the polishing is performed using 1200# sandpaper;

[0074] The etching treatment includes sequentially performing hydrochloric acid soaking treatment and alkaline solution soaking treatment; the hydrochloric acid soaking treatment includes sequentially using hydrochloric acid with a HCl mass concentration of 50% for soaking at 60°C for 10 minutes and soaking at 70°C for 10 minutes; the alkaline solution soaking treatment uses an alkaline solution of a mixture of NaOH, Na2SO4, Na2CO3, Na2SiO3 and water; based on the volume of the alkaline solution, the content of NaOH is 3g·L -1 , the content of Na2SO4 is 45g·L -1 , the content of Na2CO3 is 40g·L -1 , the content of Na2SiO3 is 15g·L -1 ;

[0075] The electro-cleaning liquid used in the electro-cleaning treatment is a mixture of sodium hydroxide, sodium carbonate, sodium phosphate, sodium silicate and water; based on the volume of the electro-cleaning liquid, the content of sodium hydroxide is 25g·L -1 , the content of sodium carbonate is 15g·L -1 , the content of sodium phosphate is 30g·L-1 , the content of sodium silicate is 15g·L -1 ; The working voltage of the electric cleaning treatment is 10V, and the working time is 30s;

[0076] The activation solution used in the activation treatment is a mixture of hydrochloric acid, sodium chloride and water; based on the volume of the activation solution, the content of hydrochloric acid is 20g·L -1 , the content of sodium chloride is 120g·L -1 ; The working voltage of the activation treatment is -10V and the working time is 30s.

[0077] 2. Brush plating is performed on the surface of the workpiece after surface treatment to form a silver-molybdenum disulfide composite coating on the surface of the workpiece;

[0078] The brush plating liquid used in the brush plating is a mixture of NiSO4·6H2O, NiCl2·6H2O, boric acid, Na2SO4, hexadecyltrimethylammonium bromide-modified nano-molybdenum disulfide, silver nitrate, formaldehyde and water; in a magnetic mixer, silver nitrate and formaldehyde are mixed with part of the water and fully stirred, and then NiSO4·6H2O, NiCl2·6H2O, boric acid, Na2SO4, hexadecyltrimethylammonium bromide-modified nano-molybdenum disulfide and the remaining water are added and fully stirred to obtain the brush plating liquid; based on the volume of the brush plating liquid, the content of NiSO4·6H2O is 90g·L -1 , NiCl2·6H2O content is 20g·L -1 , boric acid content is 10g·L -1 , the content of Na2SO4 is 40g·L -1 , the content of hexadecyltrimethylammonium bromide modified nano molybdenum disulfide is 20g·L -1 , the content of silver nitrate is 50g·L -1 , the formaldehyde content is 15g·L -1 ;

[0079] The working voltage of brush plating is 3V, and the relative movement speed between the brush plating pen and the workpiece is 2m / min. -1 , the current density is 0.3A·dm -2 , the electroplating time is 2 min; the thickness of the obtained silver-graphene composite layer is 30 μm.

[0080] Among them, the hexadecyltrimethylammonium bromide modified nano molybdenum disulfide is prepared specifically by the following method:

[0081] Mixing nano-molybdenum disulfide particles, hexadecyltrimethylammonium bromide, and ethanol in a mass ratio of 4:3:3; heating the obtained mixture to reflux reaction and standing reaction in sequence; performing solid-liquid separation on the product obtained after the reaction; washing and drying the solid phase obtained by the solid-liquid separation to obtain the hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide;

[0082] The temperature of the heating reflux reaction is 80°C, and the time of the heating reflux reaction is 22-26 hours; the temperature of the static reaction is room temperature, and the time of the static reaction is 24 hours;

[0083] Brush plating is carried out using a brush plating machine. First, the substrate to be brush plated is connected to the negative pole of the power supply as the cathode, and the brush plating pen (with a sheath) connected to the positive pole of the power supply is immersed in the brush plating solution as the anode. Relying on the action of direct current, the brush plating pen maintains contact with the workpiece under a certain pressure and performs relative movement during brush plating. The metal cations in the brush plating solution in the bath will be discharged and crystallized on the substrate to be brush plated as the cathode to form a coating; after the brush plating is completed, rinse with water, then rinse with alcohol, and finally blow dry. The high-frequency mechanical vibration of the ultrasonic cleaner is used to clean the oil wrapped on the surface of the sample, the adhering impurities and the attached fingerprints.

[0084] Example 2

[0085] This embodiment provides a composite silver-plating brush plating method.

[0086] The only difference between it and Example 1 is that: the surface of the workpiece that has completed the surface treatment is brush plated by brush plating, and the electroplating time is 3 minutes during the process of forming a silver-molybdenum disulfide composite coating on the surface of the workpiece; the thickness of the obtained silver-graphene composite layer is 32 μm.

[0087] Example 3

[0088] This embodiment provides a composite silver-plating brush plating method.

[0089] The only difference between it and Example 1 is that: the surface of the workpiece that has completed the surface treatment is brush plated by brush plating, and the electroplating time is 4 minutes during the process of forming a silver-molybdenum disulfide composite coating on the workpiece surface; the thickness of the obtained silver-graphene composite layer is 35 μm.

[0090] Example 4

[0091] This embodiment provides a composite silver-plating brush plating method.

[0092] The only difference between it and Example 1 is that: the surface of the workpiece that has completed the surface treatment is brush plated by brush plating, and in the process of forming the silver-molybdenum disulfide composite coating on the workpiece surface, the plating pressure is 4V; the thickness of the obtained silver-graphene composite layer is 34μm.

[0093] Example 5

[0094] This embodiment provides a composite silver-plating brush plating method.

[0095] The only difference between it and Example 4 is that: the surface of the workpiece that has completed the surface treatment is brush plated by brush plating, and the electroplating time is 3 minutes during the process of forming the silver-molybdenum disulfide composite coating on the workpiece surface; the thickness of the obtained silver-graphene composite layer is 33 μm.

[0096] Example 6

[0097] This embodiment provides a composite silver-plating brush plating method.

[0098] The only difference between it and Example 4 is that: the surface of the workpiece after surface treatment is brush plated by brush plating, and the plating time is 4 minutes during the process of forming a silver-molybdenum disulfide composite coating on the surface of the workpiece; the thickness of the obtained silver-graphene composite layer is 36 μm.

[0099] Example 7

[0100] This embodiment provides a composite silver-plating brush plating method.

[0101] The only difference between it and Example 1 is that: the surface of the workpiece that has completed the surface treatment is brush plated by brush plating, and in the process of forming the silver-molybdenum disulfide composite coating on the surface of the workpiece, the plating pressure is 5V; the thickness of the obtained silver-graphene composite layer is 37μm.

[0102] Example 8

[0103] This embodiment provides a composite silver-plating brush plating method.

[0104] The only difference between it and Example 7 is that: the surface of the workpiece that has completed the surface treatment is brush plated by brush plating, and the electroplating time is 3 minutes during the process of forming the silver-molybdenum disulfide composite coating on the workpiece surface; the thickness of the obtained silver-graphene composite layer is 36 μm.

[0105] Example 9

[0106] This embodiment provides a composite silver-plating brush plating method.

[0107] The only difference between it and Example 7 is that: the surface of the workpiece that has completed the surface treatment is brush plated by brush plating, and the electroplating time is 4 minutes during the process of forming the silver-molybdenum disulfide composite coating on the workpiece surface; the thickness of the obtained silver-graphene composite layer is 40 μm.

[0108] Example 10

[0109] This embodiment provides a composite silver-plating brush plating method.

[0110] The difference between the embodiment 1 and the embodiment 1 is that the surface of the workpiece after the surface treatment is subjected to brush plating. In the process of forming the silver-molybdenum disulfide composite coating on the surface of the workpiece, the content of the hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide in the brush plating solution is 5 g·L -1 .

[0111] Embodiment 11

[0112] This embodiment provides a composite silver-plating brush plating method.

[0113] The difference between the embodiment 10 and the embodiment 11 is that the surface of the workpiece after the surface treatment is subjected to brush plating. In the process of forming the silver-molybdenum disulfide composite coating on the surface of the workpiece, the content of the hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide in the brush plating solution is 10 g·L -1 .

[0114] Example 12

[0115] This embodiment provides a composite silver-plating brush plating method.

[0116] The difference between the embodiment 10 and the embodiment 11 is that the surface of the workpiece after the surface treatment is subjected to brush plating. In the process of forming the silver-molybdenum disulfide composite coating on the surface of the workpiece, the content of the hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide in the brush plating solution is 15 g·L -1 .

[0117] Embodiment 13

[0118] This embodiment provides a composite silver-plating brush plating method.

[0119] The difference between the embodiment 10 and the embodiment 11 is that the surface of the workpiece after the surface treatment is subjected to brush plating. In the process of forming the silver-molybdenum disulfide composite coating on the surface of the workpiece, the content of the hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide in the brush plating solution is 20 g·L -1 .

[0120] Embodiment 14

[0121] This embodiment provides a composite silver-plating brush plating method.

[0122] The difference between the embodiment 10 and the embodiment 11 is that the surface of the workpiece after the surface treatment is subjected to brush plating. In the process of forming the silver-molybdenum disulfide composite coating on the surface of the workpiece, the content of the hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide in the brush plating solution is 25 g·L -1 .

[0123] Embodiment 15

[0124] This embodiment provides a composite silver-plating brush plating method.

[0125] The difference between the embodiment 10 and the embodiment 11 is that the surface of the workpiece after the surface treatment is subjected to brush plating. In the process of forming the silver-molybdenum disulfide composite coating on the surface of the workpiece, the content of the hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide in the brush plating solution is 30 g·L -1 .

[0126] Example 16

[0127] This embodiment provides a composite silver-plating brush plating method.

[0128] The only difference between the embodiment 1 and the embodiment 1 is that the brush plating solution does not use hexadecyltrimethylammonium bromide-modified nano-molybdenum disulfide but uses unmodified nano-molybdenum disulfide.

[0129] Comparative Example 1

[0130] This comparative example provides a silver brush plating method.

[0131] The difference between it and Example 1 is that: the surface of the workpiece that has completed the surface treatment is brush plated by brush plating, and a pure silver plating layer rather than a silver-graphene composite layer is formed on the surface of the workpiece; specifically, the only difference from Example 1 is that the raw material composition of the brush plating solution used does not contain hexadecyltrimethylammonium bromide-modified nano-molybdenum disulfide.

[0132] Comparative Example 2

[0133] This comparative example provides a composite silver-plating brush plating method.

[0134] The only difference between it and comparative example 1 is that in the process of plating the silver-graphene composite layer on the aluminum-based surface of the electrical contact component that has been pre-plated with a copper layer by brush plating, the plating pressure is 4V.

[0135] Comparative Example 3

[0136] This comparative example provides a composite silver-plating brush plating method.

[0137] The only difference between it and comparative example 1 is that in the process of plating the silver-graphene composite layer on the aluminum-based surface of the electrical contact component that has been pre-plated with a copper layer by brush plating, the plating pressure is 5V.

[0138] Experimental Example 1

[0139] The effect of different addition amounts of hexadecyltrimethylammonium bromide modified nano molybdenum disulfide (CTAB-MoS2) on the cross-sectional morphology of the composite coating was tested.

[0140] The cross-sectional morphology and thickness of the composite coating (silver-molybdenum disulfide coating) prepared in Example 10, Example 12, Example 14, and Example 15 were tested respectively.

[0141] The thickness of the composite coating prepared in Example 10, Example 12, Example 14 and Example 15 is shown in Table 1, and the cross-sectional morphology is shown in Table 1. Figure 8 shown.

[0142] Table 1

[0143]

[0144]

[0145] From Table 1, Figure 8 ( Figure 8 In, a, b, c, d are successively the composite coating prepared by embodiment 10, embodiment 12, embodiment 14, embodiment 15) It can be known that when the addition amount of cetyl trimethyl ammonium bromide modified nano molybdenum disulfide is 5-25g / L, the thickness of the composite coating is constantly increasing. The composite coating surface formed when the addition amount of cetyl trimethyl ammonium bromide modified nano molybdenum disulfide is 5g / L and 15g / L is tortuous. The composite coating surface formed when the addition amount of cetyl trimethyl ammonium bromide modified nano molybdenum disulfide is 25g / L tends to be flat, and the pores inside the composite coating formed when cetyl trimethyl ammonium bromide modified nano molybdenum disulfide are also the least. Show that in the composite coating formed when the addition amount of cetyl trimethyl ammonium bromide modified nano molybdenum disulfide is 25g / L, the combination rate of molybdenum disulfide and silver in the coating is high, the porosity is low, and the composite coating has a low porosity and can prevent the corrosive medium from the outside from entering the coating, thereby improving the corrosion resistance of the composite coating. When the addition amount of hexadecyltrimethylammonium bromide-modified nano-molybdenum disulfide reaches 30g / L, although the thickness of the composite coating increases, the composite coating becomes uneven and the porosity increases. This is because the adhesion of the composite coating is weakened, resulting in a decrease in the bonding force, causing partial detachment of the composite coating.

[0146] Experimental Example 2

[0147] The effect of different addition amounts of hexadecyltrimethylammonium bromide modified nano molybdenum disulfide (CTAB-MoS2) on the surface morphology of the composite coating was tested.

[0148] The surface morphology of the composite coating (silver-molybdenum disulfide coating) prepared in Examples 10 to 15 was tested respectively. The results are as follows Fig. 9 As shown, Fig. 9 In the figure, a, b, c, d, e, and f are the surface morphologies of the composite coatings of Example 10 to Example 15, respectively.

[0149] Depend on Fig. 9 It can be seen that the amount of hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide added has a significant effect on the quality and density of the silver-molybdenum disulfide composite coating. When the amount of hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide added is 5g / L, the composite coating is relatively sparse, the number of molybdenum disulfide particles in the coating is small, and a dense coating cannot be formed (see Fig. 9 As the amount of hexadecyltrimethylammonium bromide-modified nano-molybdenum disulfide added increases, more molybdenum disulfide particles are transported and adsorbed on the cathode surface of the brush plating machine, so that the thickness of the final composite coating increases (e.g. Figure 2 d)). However, when the addition amount of hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide reaches 10g / L to 15g / L, the composite coating still presents a relatively loose state (see Figure 2 b and c). When the amount of hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide added increased to 20 g / L, the composite coating became dense and uniform (see Figure 2 d) in the above). Further increasing the amount of hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide addition will not significantly change the microscopic morphology of the composite coating, but will reduce the coating thickness because high concentrations of hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide particles will agglomerate to a certain extent and affect the electrodeposition rate. The addition amount of hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide of 20g / L is the best choice, which can further improve the coating quality and improve the electrodeposition efficiency.

[0150] Experimental Example 3

[0151] The hardness changes of composite coating and pure silver coating under different voltage and brush plating time conditions were tested.

[0152] The hardness of the composite coatings (silver-molybdenum disulfide coatings) prepared in Examples 1 to 9 and the pure silver coatings in Comparative Examples 1 to 3 were tested respectively.

[0153] During the hardness test, 5 points are randomly selected for hardness testing on each sample to be tested, and the average value of the hardness test results of the 5 points is taken as the hardness of the sample to be tested.

[0154] The results are shown in Table 2.

[0155] Table 2

[0156]

[0157] As shown in Table 2, the hardness of the pure silver coating and the composite coating (silver-molybdenum disulfide coating) under the same process conditions is compared, and it can be seen that the hardness of the coating after adding molybdenum disulfide decreases. Under the condition of constant brush plating time, the hardness increases significantly with the increase of brush plating voltage, which plays a role in surface strengthening and also improves the wear resistance of the substrate to a certain extent. When the brush plating voltage is the same, as the brush plating time increases, the coating becomes thicker, and the hardness of the composite coating will increase significantly, but too long a brush plating time will lead to a large coating thickness, causing excessive stress, thereby affecting the hardness of the coating.

[0158] Experimental Example 4

[0159] Test the effect of the addition amount of hexadecyltrimethylammonium bromide modified nano molybdenum disulfide (CTAB-MoS2) on the hardness of the coating

[0160] The hardness of the composite coatings (silver-molybdenum disulfide coatings) prepared in Examples 10 to 15 and the pure silver coating of Comparative Example 1 were tested respectively.

[0161] During the hardness test, 5 points are randomly selected for hardness testing on each sample to be tested, and the average value of the hardness test results of the 5 points is taken as the hardness of the sample to be tested.

[0162] The results are shown in Table 3.

[0163] Table 3

[0164]

[0165] As shown in Table 3, the average hardness of the pure silver coating is 129.6HV. The average hardness of the silver-molybdenum disulfide composite coating increases with the increase of the amount of hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide added, and when the amount of hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide added reaches 25g / L, the hardness of the silver-molybdenum disulfide composite coating no longer increases significantly with the increase of the amount of hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide added. The average hardness of the pure silver coating is slightly higher than the average hardness of the silver-molybdenum disulfide composite coating with a hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide addition of 20g / L.

[0166] The reason why the average hardness of the silver-molybdenum disulfide composite coating increases with the increase of the amount of hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide is that with the increase of the amount of hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide, the combination efficiency of molybdenum disulfide particles and silver in the coating increases, and the molybdenum disulfide is evenly dispersed in the coating, and is wrapped into the coating in the form of inclusions, which has a certain blocking effect on the dislocation movement and plastic flow of the grains, thus producing a dispersion strengthening effect. Therefore, as the amount of hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide increases, the strengthening effect is enhanced and the hardness increases. When the amount of hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide reaches 25g / L, the combination of molybdenum disulfide particles and silver is close to saturation, the strengthening effect does not change much, and the hardness no longer increases significantly.

[0167] As a reinforcing phase, MoS2 has a unique geometric shape and two-dimensional sheet structure, which provides two-sided interaction and is an ideal material for stress exchange with the matrix. At present, the reinforcement mechanisms of MoS2-reinforced metal matrix composites mainly include load transfer mechanism, dislocation strengthening, fine grain strengthening, etc. Depending on the process conditions, various reinforcement mechanisms work together to strengthen the matrix, rather than acting alone. Therefore, the hardness of the coating should be improved after adding MoS2.

[0168] In the actual measured data, the average hardness of the pure silver coating is slightly higher than the average hardness of the silver-molybdenum disulfide composite coating with a 20g / L addition of hexadecyltrimethylammonium bromide-modified nano-molybdenum disulfide. The reason is that the molybdenum disulfide in the plating solution has agglomeration. Agglomeration makes it unevenly dispersed in the composite material. The agglomerated molybdenum disulfide will form a lot of resistance during the transmission and separation process, reducing the transmission efficiency and separation effect of molybdenum disulfide, resulting in the hardness value of the silver-molybdenum disulfide composite coating decreasing instead of increasing.

[0169] Experimental Example 5

[0170] Analysis of corrosion resistance of composite coating and pure silver coating under different voltage and brush plating time conditions.

[0171] The composite coatings (silver-molybdenum disulfide coatings) prepared in Examples 1 to 9 and the pure silver coatings prepared in Comparative Examples 1 to 3 were tested for electrochemical parameters.

[0172] Specifically test the potentiodynamic polarization curve, self-corrosion potential, self-corrosion current density and impedance (the equivalent circuit of impedance test is as follows Figure 4 shown).

[0173] The self-corrosion potential and self-corrosion current density are shown in Table 4. The potential polarization curve is shown in Figure 1 , Figure 2 , Figure 3The impedance test results are shown in Figure 5 , Figure 6 , Figure 7 shown.

[0174] Table 4

[0175]

[0176]

[0177] The potentiodynamic polarization curves of the pure silver coating of Comparative Example 1 and the composite coating of Example 1 in 3.5% NaCl solution are shown in FIG. Figure 1 As shown. For electrochemical corrosion, the self-corrosion potential can explain the corrosion tendency of the alloy, and the self-corrosion current density can be used to indicate its corrosion rate. Compared with the pure silver coating, the potentiodynamic polarization curve of the composite coating in 3.5% NaCl solution shows a lower self-corrosion potential, which indicates that the potential for the start of corrosion is more negative, that is, it is easier to start corrosion. The self-corrosion current density of the composite coating is smaller than that of the pure silver coating, which means that the corrosion rate is slower, indicating that the corrosion resistance of the composite coating has improved. This phenomenon can be attributed to the addition of molybdenum disulfide. Molybdenum disulfide and silver are co-deposited into the composite coating, which not only increases the density of the coating, but also because of the chemical stability of molybdenum disulfide itself, it can effectively cover the surface of the grains and properly isolate the direct contact between the corrosive medium and the grains or grain boundaries. Thereby improving the corrosion resistance of the composite coating. The potentiodynamic polarization curves of the composite coating under different brush plating voltages in 3.5% NaCl solution are shown in Figure 2 As shown in the figure, it can be found that within the same brush plating time, when the brush plating voltage is 3V, the corrosion potential of the coating is the most positive and the corrosion tendency is the smallest; for the corrosion current density, it is also the smallest when the brush plating voltage is 3V, indicating that when the brush plating voltage is 3V, the corrosion resistance of the sample is the best. The potentiodynamic polarization curves of the silver-molybdenum disulfide composite coating in 3.5% NaCl solution under different brush plating times are shown in the figure. Figure 3 As shown, it can be found that under the same brush plating voltage, the longer the brush plating time, the greater the corrosion tendency and the faster the corrosion, so at 2 minutes, the corrosion resistance of the sample is the best.

[0178] The Nyquist diagram was drawn based on the impedance spectrum test results of the composite coating (the results are shown in Figure 5 ) and Bode plots (results as shown Figure 6 , Figure 7 The Nyquist plot is a plot of the imaginary part of impedance (-Z") versus the real part of impedance (Z'). The larger the radius of the arc in the plot, the greater the polarization resistance and the better the corrosion resistance. Figure 5 It can be seen that the composite coating exhibits a higher impedance value when the brush plating voltage is 3V and the brush plating time is 2min and 3min. It can be inferred that the samples under these two process conditions have good corrosion resistance. Figure 6 (Logarithmic graph of Bode impedance modulus |Z| and frequency f) It can be observed that the impedance modulus of the composite coating in the low-frequency region is relatively high when the brush plating voltage is 3V and the brush plating time is 2min and 3min. At present, the lowest frequency impedance modulus (|Z|0.01Hz) is generally used as the standard for evaluating the protective performance of the coating. The higher the value of |Z|0.01Hz, the better the corrosion resistance, and vice versa. Therefore, the change trend of |Z|0.01Hz is consistent with the phenomenon reflected in the Nyquist diagram. Figure 7 (The logarithmic graph of Bode phase angle and frequency) also shows that the phase angle of the coating when the brush plating voltage is 3V and the brush plating time is 2min and 3min is significantly higher than that of the coating under other process conditions, indicating that the composite coating has better corrosion resistance when the brush plating voltage is 3V and the brush plating time is 2min and 3min.

[0179] Experimental Example 6

[0180] Analysis of corrosion resistance of coatings with different addition amounts of cetyltrimethylammonium bromide modified nano molybdenum disulfide (CTAB-MoS2).

[0181] Electrochemical parameter tests were performed on the composite coatings (silver-molybdenum disulfide coatings) prepared in Examples 10 to 15, respectively.

[0182] Specifically test the potentiodynamic polarization curve and impedance (the equivalent circuit of the impedance test is as follows Fig.11 shown).

[0183] Potential polarization curve Fig.10 The impedance test results are shown in Fig.12 , Fig.13 , Fig.14 shown.

[0184] For electrochemical corrosion, the corrosion potential can indicate the corrosion tendency of the alloy, while the corrosion current can be used to indicate its corrosion rate. The potentiodynamic polarization curves of the silver-molybdenum disulfide composite coating obtained under different addition amounts of hexadecyltrimethylammonium bromide-modified nano-molybdenum disulfide (CTAB-MoS2) in 3.5% NaCl solution are shown in Fig.10As shown. The self-corrosion potential of the silver-molybdenum disulfide composite coating when the addition amount of hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide is 25g / L is lower than that of the other groups, indicating that the corrosion of the composite coating when the addition amount of hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide is more difficult to start. The self-corrosion current of the silver-molybdenum disulfide composite coating when the addition amount of hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide is 25g / L is smaller than that of the other groups, proving that its corrosion resistance is better than that of the other groups. The reason may be that with the increase of the addition amount of hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide, the combination efficiency of molybdenum disulfide particles and silver increases, more molybdenum disulfide and silver co-deposit into the composite coating and distribute in the grains and grain boundaries, increasing the density of the coating, and molybdenum disulfide itself has stable chemical properties and high hydrophobicity, which can cover the surface of the grains and properly isolate the direct contact between the corrosive medium and the grains or grain boundaries, thereby improving the corrosion resistance of the composite coating. It can be seen that the corrosion resistance of the composite coating is relatively good when the addition amount of hexadecyltrimethylammonium bromide modified nano molybdenum disulfide is 25g / L.

[0185] According to the impedance spectrum test results of the composite coating, the Nyquist diagram and Bode diagram were drawn. The Nyquist diagram is a diagram of the imaginary part of the impedance (-Z") versus the real part of the impedance (Z'). The larger the radius of the arc in the Nyquist diagram, the greater the polarization resistance and the better the corrosion resistance. Fig.12 It can be seen that the silver-molybdenum disulfide composite coating shows a higher impedance value when the addition amount of hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide is 5g / L and 30g / L, indicating that the two composite coatings have good corrosion resistance. Fig.13 It can be observed from the logarithmic graph of Bode impedance modulus |Z| and frequency f that the impedance modulus of the composite coatings with 5g / L and 30g / L of hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide additions in the low-frequency region is relatively high. At present, the lowest frequency impedance modulus (|Z|0.01Hz) is generally used as the standard for evaluating the protective performance of coatings. The higher the value of |Z|0.01Hz, the better the corrosion resistance, and vice versa. Therefore, the change trend of |Z|0.01Hz is consistent with the phenomenon reflected in the Nyquist diagram. The logarithmic graph of Bode phase angle and frequency also shows that the phase angles of the coatings with 5g / L and 30g / L of hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide additions are significantly higher than those of the coatings with other hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide additions. Overall, the silver-molybdenum disulfide composite coatings with 5g / L and 30g / L of hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide additions have better corrosion resistance.

[0186] Experimental Example 7

[0187] Phase analysis of composite coatings.

[0188] XRD tests were performed on the composite coatings prepared in Examples 10 to 15, XRD tests were performed on the composite coatings prepared in Examples 1 to 3 and 16, and EDS tests were performed on the composite coating prepared in Example 2.

[0189] Among them, the XRD patterns of the composite coatings prepared in Examples 10 to 15 are as follows: Fig.15 As shown, the XRD spectra of the composite coatings prepared in Examples 1 to 3 and the pure silver coating prepared in Comparative Example 1 are as follows: Fig.16 As shown, the EDS spectrum and element distribution of the composite coating prepared in Example 2 are as follows Fig.17 As shown ( Fig.17 (a is the SEM image, b is the EDS spectrum, c is the distribution of silver elements, and d is the distribution of Mo elements).

[0190] Depend on Fig.15 It can be seen that the silver-molybdenum disulfide composite coating has obvious diffraction peaks at 2θ=38.106°, 44.298°, 51.116°, 64.504°, 74.286°, and 78.851°. The PDF card is consistent with that of Silver-Mo, and the dominant growth plane is (111). The diffraction peaks of the silver-molybdenum disulfide composite coating obtained under six different conditions of hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide addition in Example 10-Example 15, the silver-molybdenum disulfide composite coating obtained when the hexadecyltrimethylammonium bromide modified nano-molybdenum disulfide addition is 15g / L has good bonding with the substrate. The XRD spectra of the silver-molybdenum disulfide composite coatings obtained under the six different conditions of adding amounts of hexadecyltrimethylammonium bromide-modified nano-molybdenum disulfide in Examples 10 to 15 do not show obvious characteristic peaks of substances other than Ag, Cu and Mo, indicating that the content of other impurity phases in the prepared silver-molybdenum disulfide composite coatings is low.

[0191] Fig.16 The XRD spectra of the composite coatings obtained with or without the use of CTAB to improve molybdenum disulfide and under different brush plating time conditions are shown. Fig.16 It shows that the composite coating is mainly composed of MoS2 and Ag phases. The strength of MoS2 increases with the increase of brush plating time, and the bonding efficiency of Ag and MoS2 in the composite coating improved by CTAB is also improved.

[0192] Depend on Fig.17 The energy spectrum and element distribution diagram of the silver / molybdenum disulfide composite coating prepared under the brush plating time of 3min and the brush plating voltage of 3V. Fig.17It can be seen that there are obvious diffraction peaks of silver and molybdenum disulfide elements in the silver-molybdenum disulfide composite coating, among which the diffraction peak of silver element is the strongest and the Mo peak is relatively weak. This is because the content of molybdenum disulfide in the coating is much less than that of Ag. Fig.17 Figures c and d are schematic diagrams of the distribution of silver and Mo elements in the silver-molybdenum disulfide composite coating, respectively. Fig.17 The distribution of silver elements in the coating in c presents a uniform green dot matrix. Fig.17 The orange dots in d represent the distribution of Mo in the coating. It can be seen that silver and molybdenum disulfide are evenly distributed in the coating without obvious agglomeration, which shows that the brush plating process used in this experiment can produce a relatively uniformly dispersed coating.

[0193] The element content of the silver-molybdenum disulfide composite coating prepared by brush plating time 3min and brush plating voltage 3V was measured, and the results are shown in Table 5. It can be found that the Mo element content in the silver-molybdenum disulfide composite coating is 17.96%, which proves the presence of molybdenum disulfide in the silver-molybdenum disulfide composite coating.

[0194] Table 5

[0195] element Line Type wt% Wt%Sigma At% Mo K-line system 2.42 0.1 17.96 Ni K-line system 0.17 0.04 0.26 S K-line system 2.14 0.05 3.01 Ag L Line 95.26 0.11 78.77 Total 100 100

[0196] Experimental Example 8

[0197] Analysis of conductivity and wear resistance of composite coatings.

[0198] The wear resistance of the coatings of Example 1, Example 16 and Comparative Example 1 was tested respectively. Fig.18 .

[0199] Fig.18 The surface morphologies of different coatings after the reciprocating sliding friction and wear tester test are shown, wherein (a) is the friction and wear morphology of the pure silver coating prepared in Comparative Example 1, (b) is the friction and wear morphology of the silver-molybdenum disulfide composite coating without CTAB prepared in Example 16, and (c) is the friction and wear morphology of the silver-molybdenum disulfide composite coating with CTAB prepared in Example 1. The wear of the composite coating modified with CTAB after the friction and wear test is better than that of the single silver coating and the composite coating without CTAB modification. The coating is not completely worn away, and the defects after wear are less than those of the other two coatings.

[0200] The conductivity test was performed on the coatings of Example 1, Example 16 and Comparative Example 1. The results are shown in Table 6.

[0201] As shown in Table 6, the contact resistances of the single silver coating prepared in Comparative Example 1, the silver-molybdenum disulfide composite coating without CTAB prepared in Example 16, and the silver-molybdenum disulfide composite coating material modified by CTAB prepared in Example 1 are shown. It can be seen that the initial contact resistance and the final contact resistance of the modified coating material are smaller than those of the single silver coating and the unmodified composite coating material, which indicates that the conductive properties of the composite coating modified by CTAB are improved.

[0202] Table 6

[0203]

[0204]

[0205] The embodiments described above are for better explaining the present invention. For technical researchers in the field, it is not difficult to make various modifications to these embodiments without departing from the principles and spirit of the present invention. Therefore, the present invention is not limited to the embodiments herein. The improvements and changes made by those skilled in the art to the present invention according to the principles and spirit of the present invention should be within the protection scope of the present invention.

Claims

1. A composite silver-plating brush plating solution, wherein: The raw materials of the brush plating solution include: silver nitrate, molybdenum disulfide, formaldehyde and solvent; Based on the volume of the brush plating solution, the content of silver nitrate is 40-60g·L -1 , the content of molybdenum disulfide is 5-30g·L -1 , the formaldehyde content is 10-20g·L -1 .

2. The brush plating solution according to claim 1, wherein Based on the volume of the brush plating solution, the content of molybdenum disulfide is 20-25g·L -1 .

3. The brush plating solution according to claim 1, wherein: Molybdenum disulfide is made of hexadecyltrimethylammonium bromide modified nano molybdenum disulfide; Preferably, the hexadecyltrimethylammonium bromide modified nano molybdenum disulfide is prepared by the following method: Mixing nano-molybdenum disulfide particles, hexadecyltrimethylammonium bromide, and an alcohol solvent; heating the obtained mixture to reflux and standing to react in sequence; performing solid-liquid separation on the product obtained after the reaction; washing and drying the solid phase obtained by the solid-liquid separation to obtain the hexadecyltrimethylammonium bromide-modified nano-molybdenum disulfide; The temperature of the heating reflux reaction is 75-85°C, and the time of the heating reflux reaction is 22-26h; the temperature of the static reaction is room temperature, and the time of the static reaction is 22-26h; More preferably, the alcohol solvent is ethanol; More preferably, the mass ratio of the nano-molybdenum disulfide particles to the hexadecyltrimethylammonium bromide is 1-6:

1.

4. The brush plating solution according to claim 1, wherein The raw material composition of the brush plating solution also includes nickel salt; based on the volume of the brush plating solution, the content of the nickel salt is 100-120g·L -1 ; Preferably, the nickel salt includes NiSO4·6H2O and NiCl2·6H2O; More preferably, based on the volume of the brush plating solution, the content of NiSO4·6H2O is 80-100 g·L -1 ; More preferably, based on the volume of the brush plating solution, the content of NiCl2·6H2O is 10-30 g·L -1 .

5. The brush plating solution according to claim 1, wherein: The raw material composition of the brush plating solution also includes boric acid; based on the volume of the brush plating solution, the content of boric acid is 5-15g·L -1 .

6. The brush plating solution according to claim 1, wherein: The raw material composition of the brush plating solution also includes sodium sulfate; based on the volume of the brush plating solution, the content of sodium sulfate is 30-50g·L -1 .

7. The brush plating solution according to claim 1, wherein: The solvent used is water.

8. A composite silver-plating brush plating method, the method comprising: The composite silver-plating brush plating solution according to any one of claims 1 to 7 is used to perform brush plating on the surface of a workpiece to form a silver-molybdenum disulfide composite coating on the surface of the workpiece.

9. The brush plating method according to claim 8, wherein: During the brush plating process, the working voltage of the brush plating is 3-5V, and the relative movement speed between the brush plating pen and the workpiece is 2-4m·min -1 , current density is 0.1-0.5A·dm -2 , the electroplating time is 2-4min.

10. The brush plating method according to claim 8, wherein: The thickness of the silver-molybdenum disulfide composite coating formed on the surface of the workpiece is 30-40 μm.

11. The brush plating method according to claim 8, wherein: The composite silver brush plating method also includes: Before the workpiece surface is electro-brush plated, the workpiece surface is treated; The surface treatment of the workpiece surface includes: grinding, etching, electro-cleaning and activation of the workpiece surface in sequence.

12. The brush plating method according to claim 11, wherein: The grinding process includes: coarse grinding, fine grinding and polishing in sequence. Coarse grinding is performed using 800# sandpaper, fine grinding is performed using 1000# sandpaper, and polishing is performed using 1200# sandpaper.

13. The brush plating method according to claim 11, wherein: The etching treatment includes sequentially performing a hydrochloric acid immersion treatment and an alkaline solution immersion treatment.

14. The brush plating method according to claim 8, wherein: The workpiece surface material is copper.

15. A composite coating, wherein: The composite coating is prepared by the composite silver-plating brush plating method according to any one of claims 8 to 14.